A Robust Microfluidic Device for the Synthesis and Crystal Growth of Organometallic Polymers with Highly Organized Structures1. (12th December 2014) - Liu, Xiao; Yi, Qiaolian; Han, Yongzhen; Liang, Zhenning; Shen, Chaohua; Zhou, Zhengyang; Sun, Jun‐liang; Li, Yizhi; Du, Wenbin; Cao, Rui
Abstract A simple and robust microfluidic device was developed to synthesize organometallic polymers with highly organized structures. The device is compatible with organic solvents. Reactants are loaded into pairs of reservoirs connected by a 15 cm long microchannel prefilled with solvents, thus allowing long‐term counter diffusion for self‐assembly of organometallic polymers. The process can be monitored, and the resulting crystalline polymers are harvested without damage. The device was used to synthesize three insoluble silver acetylides as single crystals of X‐ray diffraction quality. Importantly, for the first time, the single‐crystal structure of silver phenylacetylide was determined. The reported approach may have wide applications, such as crystallization of membrane proteins, synthesis and crystal growth of organic, inorganic, and polymeric coordination compounds, whose single crystals cannot be obtained using traditional methods.